Sociology : a global perspective - Ferrante-Wallace, Joan, 1955- (Stamford, CT : Cengage Learning, 2015)
In a changing world, it is now more vital than ever to understand how the beliefs, traditions, and experiences of individuals in other countries affect us all. Ferrante's trademark approach continues in this edition: in each chapter, she emphasizes a country or an interconnection between the United States and another country and masterfully weaves together and applies sociological concepts and theories to important issues in United States and the world, to help you see your own country and others in the way sociologists do.
1. The Sociological Imagination: With Emphasis on Globalization and Glocalization --- 2. Sociological Perspectives and Methods of Research: With Emphasis on Social Robotics --- 3. Culture: With Emphasis on Transcultural Encounters and Exchanges --- 4. Socialization: With Emphasis on In-Groups and Out-Groups --- 5. Social Interaction and Impression Management: With Emphasis on Relationships in a Digital Age --- 6. Formal Organizations: With Emphasis on Industrial Food --- 7. Deviance, Conformity, and Social Control: With Emphasis on Mass Surveillance --- 8. Social Inequality: With Emphasis on Social Mobility --- 9. Race and Ethnicity: With Emphasis on Social Construction --- 10. Gender and Sexualities: With Emphasis on Gender Ideals --- 11. Economics and Politics: With Emphasis on India and Its IT Professionals --- 12. Family: With Emphasis on the Aging Societies --- 13. Education: With Emphasis on Social Reproduction in a Knowledge Economy --- 14. Religion: With Emphasis on Religion as a Transnational Force --- 15. Population and Health Care: With Emphasis on the U.S. Health Care System --- 16. Social Change: With Emphasis on Changing Environment.
Includes bibliographical references (pages 377-398) and index.
Keywords: Sociology; Sociology -- Study and teaching; Social history -- Cross-cultural studies